The Gift of Aphrodite in Iliad 24.30. (2020) - Mancilla, Cristian
Abstract: In the famous story of Paris' choice, he favoured the goddess who offered him 'grievous lust' (μαχλοσύνην ἀλɛγɛινήν). This is what Homer tells us in Il . 24.30. It has not often been noticed that Cratinus (5th cent. BC) and Lucian (2nd cent. AD) mention another gift – that Aphrodite's bribe was to make Paris irresistible to women. This alternative version happens to correspond to a high degree with several literary and artistic representations of the same story, telling it in a manner that implies or suggests the variant account. This paper argues that the set of instances containing this alternative gift may be based on an actual episode within the oral tradition. Homer himself seems to hint at this link when he refers to the 'grievous lust' of Paris. The Homeric reference to the alternative gift was acknowledged by Herbert Rose in 1951, even though he rejected the line in Homer which mentioned the Judgement of Paris ( Il . 24.30). This seeming contradiction of Rose's accepting the alternative gift while rejecting the Judgement makes his explanation rather atypical. His uncommon viewpoint, nevertheless, will allow us to identify the presence of this alternative gift in many literary and artistic works, whether explicitly mentioned, implied, or suggested.